KEEFEKTIFAN METODE PEMBELAJARAN COOPERATIVE TIPE STAD MELALUI MEDIA PERMAINAN TWISTER UNTUK MENINGKATKAN HASIL BELAJAR KAIWA PADA MAHASISWA TINGKAT II KELAS B ANGKATAN 2017 PRODI PENDIDIKAN BAHASA JEPANG - Utami, Dwi Rianda; Sinaga, Mangatur; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to discover how the application of method Cooperative Learning type stad by using game twister and college students’ response in kaiwa lesson on II grade college students in Japanese Study Program. This research used qualitative descriptive method and the researcher was merely to explain the data which had been collected. The sample of this research was 29 university students and the research had been done in two meeting. The data collection technique used questionnaire and interview. The application of this method, half of the member of the group was active in this activity. The university students’s response in questionnaire showed 85% of them were felt helpful and easy to understand kaiwa 4 and 75% of respondents was motivated. Moreover, 100% respondents in each became more active in giving opinion and 100% respondents more active in using japanese. In contrast, more than half of respondents got difficulties in using grammar and choosing appropriate vocabulary. Besides, the students’s response according to interview found that most of students became more excited to study by interacting, cooperating, and motivating one another in a group to make their tesks.Key Words : Cooperative learning type stad, game twister, kaiwa, the effective